2021
DOI: 10.3390/ijms222413412
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Podocyte Vesicle Transcytosis and Albuminuria in APC C-Terminal Deficiency Mice with Puromycin-Induced Nephrotic Syndrome

Abstract: In minimal change nephrotic syndrome, podocyte vesicle transport is enhanced. Adenomatous polyposis coli (APC) anchors microtubules to cell membranes and plays an important role in vesicle transport. To clarify the role of APC in vesicle transport in podocytes, nephrotic syndrome was induced by puromycin amino nucleoside (PAN) injection in mice expressing APC1638T lacking the C-terminal of microtubule-binding site (APC1638T mouse); this was examined in renal tissue changes. The kidney size and glomerular area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In support of our data, Pod-Sec63/Xbp1 double-knockout mice did not exhibit different autophagosomal activity but still displayed severe ER stress [36]. This finding is surprising, considering that podocytes generally exhibit relatively high basal autophagy compared to other cell types [61,62]. Additionally, enhanced autophagy has been observed in glomerulopathies in humans, as indicated by elevated kidney ER stress in patients with MCD or FSGS [63,64].…”
Section: Discussionsupporting
confidence: 71%
“…In support of our data, Pod-Sec63/Xbp1 double-knockout mice did not exhibit different autophagosomal activity but still displayed severe ER stress [36]. This finding is surprising, considering that podocytes generally exhibit relatively high basal autophagy compared to other cell types [61,62]. Additionally, enhanced autophagy has been observed in glomerulopathies in humans, as indicated by elevated kidney ER stress in patients with MCD or FSGS [63,64].…”
Section: Discussionsupporting
confidence: 71%
“…We observed vesicles in podocytes from IMN patients with electron microscopy and found that the numbers of intracellular vesicles in podocytes from IMN patients were significantly increased (Figure 1). A previous study has reported that suppression of podocyte vesicle transport is associated with reduced albuminuria in nephritic syndrome 15 . Moreover, SNARE‐associated vesicular insertion into the plasma membrane causes podocyte actin remodelling and proteinuria 6 .…”
Section: Resultsmentioning
confidence: 97%
“…Vesicle formation plays an important role in maintaining the structure of foot processes in glomerular podocytes 22 . However, increased vesicle transcytosis is associated with foot process effacement in podocytes in nephrotic syndrome 15 . In a rat model of nephrotic syndrome induced by puromycin aminonucleoside, accumulation of blue‐labelled albumin endocytic vesicles is observed in podocytes 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations